2000
DOI: 10.1097/00003246-200001000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of leukotriene B4, peptide leukotrienes, and interleukin-8 plasma concentrations in patients at risk of acute respiratory distress syndrome and with acute respiratory distress syndrome: Mortality prognostic study

Abstract: LTs are elevated during the early phases of ARDS, whereas IL-8 increases throughout the study. The evaluation of LTB4 and IL-8 may be useful prognostic indices in patients with early phase ARDS after admission to the intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 28 publications
0
32
0
1
Order By: Relevance
“…In line with these findings, lately increased LTB4 levels in the BAL fluid were associated with enhanced pulmonary infiltration with neutrophils as well as IL-8 expression. Previously, a close association of increased IL-8 and LTB4 levels has been proposed as useful prognostic indices in patients with early phase ARDS after admission to the intensive care unit [23,25]. Nonetheless, the role of LTB4 in trauma has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these findings, lately increased LTB4 levels in the BAL fluid were associated with enhanced pulmonary infiltration with neutrophils as well as IL-8 expression. Previously, a close association of increased IL-8 and LTB4 levels has been proposed as useful prognostic indices in patients with early phase ARDS after admission to the intensive care unit [23,25]. Nonetheless, the role of LTB4 in trauma has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported elevated levels of LTB4 also in bronchoalveolar lavage (BAL) fluid from patients with ARDS or other inflammatory lung diseases such as COPD [21][22][23][24]. Moreover, the evaluation of LTB4 and IL-8 has been described as useful prognostic indices in patients with early phase ARDS after admission to the intensive care unit [23,25]. With regard to trauma patients, the data is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ketoconazole was not found to reduce the mortality or duration of mechanical ventilation in a randomized trial [20]. The beneficial effects of ketoconazole may be attributed to the inhibition of leukotriene formation as well as thromboxane A 2 synthesis [7]. The results of the present study revealed that the likelihood value of the TXB 2 levels was higher than those of the other eicosanoids examined, and that TXA 2 is a prognostic factor for sepsis patients with ARDS rather than a factor for treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Amat et al [7] analyzed the leukotrienes LTB 4 , LTC 4 and LTD 4 , and reported that only the plasma concentration of LTB 4 on day 1 was a prognostic marker for ARDS, and that LTB 4 and interleukin-8 together could be useful markers of the mortality rate. Leukotriene antagonists, such as ONO-1078 [21], LY255283 [22] and ICI 198,615 [23], seemed to ameliorate the clinical outcome in models of LPS-induced acute lung injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation